Inositol metabolism as a broad-spectrum antiviral target - Jitobaom, Kunlakanya; Auewarakul, Prasert (Frontiers in Microbiology, 2025)
Inositol plays many important roles in cellular processes through its various derivatives including phosphatidylinositol phosphates. Viruses use phosphatidylinositol phosphates for their replication in multiple processes including entry, formation of replication organelles, assembly and release. For these processes, viruses recruit phosphatidylinositol kinases to meet their demand of phosphatidylinositol phosphates. Inhibitors of phosphatidylinositol kinases have been shown to inhibit various viruses. The complexity of various types and isoforms of phosphatidylinositol kinases can be a problem in developing a broad-spectrum antiviral as different viruses use various types and isoforms of the enzyme. Inositol monophosphatase is an enzyme required for both de novo biosynthesis and intracellular recycling of inositol. It can provide a chokepoint to limit the availability of cellular inositol, phosphatidylinositol, and phosphatidylinositol phosphates. It can be a promising target for broad-spectrum antiviral development.